The impact of e-cigarette price changes on vaping and smoking behaviors. (24th August 2019) - Minami, Haruka; Teo, Terence K.
Abstract: Background: Understanding the relations between e-cigarette prices and e-cigarette/cigarette use may shed light on the possible impact of e-cigarette regulations on public health. Objectives: This study aimed to assess potential impacts of e-cigarette price changes on vaping and smoking behaviors by smoking status (current, former, and never smokers) and e-cigarette type (pre-filled only vs. refillable). Methods : A total of 918 US-based adult e-cigarette users completed an online survey, designed to assess behavioral intention of e-cigarette/cigarette use in hypothetical situations with varying prices of e-cigarettes, in 2017. Results : With reduction in e-cigarette prices, more than 50% of current smokers reported they would reduce or quit smoking, but with greater increases in price, the rates of not only those who would quit (12.5–19.4%), but also those who would increase smoking rose (15.1–25.1%). Current smokers (vs. former/never) were more likely to increase e-cigarette use at reduced e-cigarette prices. Among current smokers, pre-filled users were less likely to quit smoking with reduced prices. At higher prices, pre-filled users were more likely to quit e-cigarettes (former smokers), but also more likely to start smoking (never smokers). Among former smokers, recent quitters were more likely to restart smoking with any e-cigarette price changes, and less likely to reduce or quit e-cigarettes with increased prices. Conclusions : Both smoking and e-cigarette use seem to be sensitive to e-cigarette price changes. Increases in e-cigarette price may have both positive and negative effects on smoking behavior, and e-cigarette price changes may disproportionately affect pre-filled users and recent quitters.